Search for the rare decay Bs0→μ+μ- with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
We present a search for the flavor-changing neutral current decay Bs0→ μ+μ- using about 0.45fb-1 of data collected in pp̄ collisions at √s=1.96TeV with the D0 detector at the Fermilab Tevatron Collider. We find an upper limit on the branching ratio of this decay normalized to Bs0→J/ψ of B(Bs0→ μ+μ -)B(Bs0→J/ψ)<4.4×10-3 at the 95% C.L. Using the central value of the world average branching fraction of Bs0→J/ψ, the limit corresponds to B(Bs0→ μ+μ -)<4.1×10-6 at the 95% C.L., the most stringent upper bound to date. © 2006 The American Physical Society.